Implementation of Teaching Skills Learned by Trained Teachers for Teaching Science Subjects at Secondary School level - SAJJAD, Shahida (The Eurasia Proceedings of Educational and Social Sciences, 2018)
The given study aimed collecting facts and information about the state of professional competence of science teachers in secondary schools, and its effectiveness to communicate the requisite knowledge; where in the extent of the training given to the teachers for teaching science in secondary school is to be determined. The data was collected from nine private and nine public secondary schools located in Karachi by interviewing 54 trained teachers selected through convenience sampling, having a Bachelor of Education (B.Ed.) degree and who were teaching science subjects at secondary level of school. The results reveal that there is less coordination between the actual teaching of science in secondary schools in Karachi and the training given to the teachers for teaching science although the government spent a lot of money on this training. The ineffective teaching is due to lack of; teaching aids, laboratory facilitates in schools, and lesson planning by teacher. Mostly teachers explain the experiments through text book only. It is recommended that the schools should be supplied with audio visual aids and necessary laboratory equipment, and the teaching load on the science teacher is reduced to have enough free.